The Influence of Animated Drama Gadget Media (Gadram) on Writing Skills Learning for Class XI MAN 20 Jakarta - Mila Permatasari; Reni Nur Eriyani; Etsa Purbarani (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to describe how the planning, implementation, and assessment of learning carried out by teachers in learning to write drama texts. In the world of education, measurements consist of two types, namely tests and non-tests. This study aims to provide the influence of Gawai Drama learning media on drama learning for class XI MAN 20 Jakarta. This study uses a quantitative method. The population of this study were students of Control class XI MIPA 1 MAN 20 Jakarta totaling 36 students and students of Experiment class XI MIPA 2 MAN 20 Jakarta totaling 36 students. The research method used in this study is an experimental method with a randomized control-group pre-test post-test design technique. The instrument in this study is a table of drama text writing skills. The sample of this study was class XI MIPA 2 even semester of the 2023/2024 academic year. The research data collection techniques were observation, tests, and documentation.